Denial, Deception, and Ignorance: "Culturo-Behavior Unscience" Examined in Three Recent Books. - Rakos, Richard F.; Alavosius, Mark P.; Krispin, Jonathan V. (Behavior & Social Issues, 2025)
This article reviews three recent books that consider how science is conveyed and often misrepresented to the public and how this can corrupt broad, vexing social issues and undermine human well-being. The Parrot and the Igloo (Lipsky, 2023), Ultra-Processed People: The Science behind Food that Isn't Food (Van Tulleken, 2023), and Skin in the Game: Hidden Asymmetries in Daily Life (Taleb, 2018) offer provocative discussions of misleading accounts of increasingly important social issues, such as the impact of special interests deceiving the public, social media proliferating misinformation, the consequences of misunderstanding science, and faulty conceptions of the world that negatively affect decisions now and will affect future generations. A sophisticated understanding of these contemporary cultural dynamics can inform behavior scientists' thinking about improving the future while presenting a multitude of opportunities to advance our science and better communicate information to the public.